2017
DOI: 10.3389/fneur.2017.00507
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Outcome and Quality of Life in Adults after Status Epilepticus: A Multicenter, Longitudinal, Matched Case–Control Analysis from Germany

Abstract: BackgroundThere is a lack of data concerning socioeconomic outcome and quality of life (QoL) in patients after status epilepticus (SE) in Germany.Patients and methodsAdult patients treated between 2011 and 2015 due to SE at the university hospitals in Frankfurt, Greifswald, and Marburg were asked to fill out a questionnaire regarding long-term outcome of at least 3 months after discharge. The SE cohort consisted of 25.9% patients with an acute symptomatic, 42% with a remote symptomatic and previous epilepsy, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
3
32
0
4
Order By: Relevance
“…Neuroprotective approaches are likely to improve outcome of patients with acute symptomatic causes, which seems to be one of the most important risk factors 20. Some studies have demonstrated that functional outcome and likely QoL may improve over time 15, 18, 22, 23. Promising research in animal models is in the process of identifying biomarkers that can be modulated to minimize long‐term functional impairment 89, 90.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuroprotective approaches are likely to improve outcome of patients with acute symptomatic causes, which seems to be one of the most important risk factors 20. Some studies have demonstrated that functional outcome and likely QoL may improve over time 15, 18, 22, 23. Promising research in animal models is in the process of identifying biomarkers that can be modulated to minimize long‐term functional impairment 89, 90.…”
Section: Discussionmentioning
confidence: 99%
“…However, population‐based studies comparing adults with childhood‐onset epilepsy with or without SE showed no association with educational attainment, employment status, and income 33. Patients after RSE may achieve an equivalent QoL as compared to patients after non‐RSE 18. However, patients in seizure remission present better QoL results as compared to patients with SE 18.…”
Section: Long‐term Outcomes Of Sementioning
confidence: 97%
See 1 more Smart Citation
“…[16][17][18] The detailed evaluation of all SE patients is part of a study on SE outcomes; this study was registered at the German Clinical Trials Register (DRKS00008718) and was approved by both local ethics committees. Both hospitals offer a full range of neurological care services with expertise in epileptology and intensive care medicine.…”
Section: Study Settings and Designmentioning
confidence: 99%
“…Unfortunately, 31%-43% of patients with established SE will become refractory to first-line AEDs. 2,11 Both RSE and SRSE can cause long-term neurological disability and reduced quality of life compared with those in seizure remission, 2,11,14 highlighting the unmet need for novel and effective SE treatments. 7,12,13 SRSE is SE that has continued or recurred despite 24 hours of general anesthesia and has an estimatedmortalityrateof30%-50%.…”
mentioning
confidence: 99%